Mitochondrial resilience and antioxidant defence against HIV-1: unveiling the power of Asparagus racemosus extracts and Shatavarin IV - Jadaun, Pratiksha; Harshithkumar, R.; Seniya, Chandrabhan; Gaikwad, Shraddha Y.; Bhoite, Shubhangi P.; Chandane-Tak, Madhuri; Borse, Swapnil; Chavan-Gautam, Preeti; Tillu, Girish; Mukherjee, Anupam (Frontiers in Microbiology, 2024)
Asparagus racemosus (AR), an Ayurvedic botanical, possesses various biological characteristics, yet its impact on HIV-1 replication remains to be elucidated. This study aimed to investigate the inhibitory effects of AR root extracts and its principal bioactive molecule, Shatavarin IV (Shatavarin), on HIV-1 replication and their role in mitigating mitochondrial dysfunction during HIV-1 infection, utilizing both in vitro and in silico methodologies. The cytotoxicity of the extracts was evaluated using MTT and ATPlite assays. In vitro anti-HIV-1 activity was assessed in TZM-bl cells against X4 and R5 subtypes, and confirmed in peripheral blood mononuclear cells using HIV-1 p24 antigen capture ELISA and viral copy number assessment. Mechanistic insights were obtained through enzymatic assays targeting HIV-1 Integrase, Protease and Reverse Transcriptase. Shatavarin's activity was also validated via viral copy number and p24 antigen capture assays, along with molecular interaction studies against key HIV-1 replication enzymes. HIV-1 induced mitochondrial dysfunction was evaluated by detecting mitochondrial reactive oxygen species (ROS), calcium accumulation, mitochondrial potential, and caspase activity within the infected cells. Non-cytotoxic concentrations of both aqueous and hydroalcoholic extracts derived from Asparagus racemosus roots displayed dose-dependent inhibition of HIV-1 replication. Notably, the hydroalcoholic extract exhibited superior Reverse Transcriptase activity, complemented by moderate activity observed in the Protease assay. Molecular interaction studies revealed that Shatavarin IV, the key bioactive constituent of AR, formed hydrogen bonds within the active binding pocket site residues crucial for HIV replication enzyme catalysis, suggesting its potential in attenuating HIV-1 infection. Mitochondrial dysfunction induced by HIV-1 infection, marked by increased oxidative stress, mitochondrial calcium overload, loss of mitochondrial membrane potential, and elevated caspase activity, was effectively mitigated by treatment with AR extracts and Shatavarin IV. These findings underscore the potential of AR extracts and Shatavarin IV as antiviral agents, while enhancing mitochondrial function during HIV-1 infection. In conclusion, Asparagus racemosus extracts, particularly Shatavarin IV, demonstrate promising inhibitory effects against HIV-1 replication while concurrently ameliorating mitochondrial dysfunction induced by the virus. These findings suggest the therapeutic potential of AR extracts and Shatavarin in combating HIV-1 infection and improving mitochondrial health.